Love and ruin [compact disc, unabridged] : a novel - McLain, Paula (Random House Audio, 2018)
The bestselling author of The Paris Wife returns to the subject of Ernest Hemingway in a novel about his passionate, stormy marriage to Martha Gellhorn, a fiercely independent, ambitious young woman who would become one of the greatest war correspondents of the twentieth century.